Perancangan Website sebagai Media Promosi Digital pada UMKM Empek-Empek Ayuk Sarti - Tarisa Amimi; Mutia Aulia; Sularno Sularno (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2025)
This article describes the design of a website as a digital promotion medium for the micro, small, and medium enterprise (MSME) Empek-Empek Ayuk Sarti using the Webflow platform. The purpose of this community service activity is to help MSMEs expand their digital marketing reach and strengthen their professional image. The method used was a qualitative descriptive approach through observation, interviews, and direct website design implementation. The results show that the use of Webflow makes the website creation process easier, even for users without programming skills. The resulting website features product information, company profiles, and contact pages that enhance accessibility and marketing effectiveness. This activity demonstrates that simple website design training can significantly improve MSME digital competence and promotional impact.